Comparative assessment of corrosion behaviour of mild steels 3, 20 and 08KP in tap water - Vasyliev, Georgii; Brovchenko, Alina; Herasymenko, Yuriy (Publishing House of Lviv Polytechnic National University, 2013)
Comparative assessment of corrosion stability of mild steels 3, 20 and 08KP in tap water was conducted. Similar corrosion behavior of these steels was shown by weight loss, linear polarization resistance and polarization curves techniques both for pretreated and corroded surfaces. The discrepancy of the results obtained with the LPR and weight loss techniques was found out and its possible reasons were discussed. Проведена порівняльна оцінка корозійної стійкості маловуглецевих сталей 3, 20 і 08КП у водогінній воді. Методами масометрії, потенціодинамічних поляризаційних кривих і поляризаційного опору показана подібність корозійної поведінки цих сталей як на свіжезачищеній поверхні, так і після трьох тижнів експозиції. Встановлено розходження результатів вимірювання швидкості корозії методами поляризаційного опору і масометрії та наведено можливі його причини.
Порівняльна характеристика корозійної поведінки маловуглецевих сталей 3, 20 ТА 08КП у водогінній воді
Keywords: corrosion; mild steel; water supply; corrosion monitoring; polarization resistance; корозія; маловуглецева сталь; водопостачання; корозійний моніторинг; поляризаційний опір